The Effect of the Physical Work Environment and Work Motivation on Employee Performance at the Muara Pinang District Office, Empat Lawang Regency - Harsa Yurega; Yuliansyah M.Diah; Laili Dimyati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of the physical work environment and work motivation on employee performance at the Muara Pinang Subdistrict Office in Empat Lawang Regency. The research method used was a quantitative approach with a saturation sampling technique involving 43 employees. Data were collected through a questionnaire and analyzed using multiple linear regression with the aid of SPSS. Based on the results of the multiple linear regression analysis, the following multiple linear regression equation was obtained: Y = 12.515 + 0.280 X1 + 0.458 X2. The results of the study indicate that, when analyzed partially, the Physical Work Environment variable has a calculated t-value of 1.992 with a significance level of 0.053. Since the significance level is greater than 0.05 and the calculated t-value is less than the critical t-value (1.992 < 2.021), the Physical Work Environment variable does not have a significant effect. Meanwhile, Work Motivation has a calculated t-value of 3.552 with a significance level of 0.001. Since the significance level is less than 0.05 and the calculated t-value is greater than the critical t-value (3.552 > 2.021), the Work Motivation variable has a positive and significant effect. Simultaneously, the Physical Work Environment and Work Motivation have a significant effect on employee performance with a significance level of 0.000 < 0.05. This means that the most dominant variable influencing employee performance is Work Motivation. Based on the research findings, it is recommended that the Muara Pinang Subdistrict Office further enhance employee motivation and continue to pay attention to the work environment in order to support improved employee performance.